Synthesis of Sub‐2 nm Iron‐Doped NiSe2 Nanowires and Their Surface‐Confined Oxidation for Oxygen Evolution Catalysis - Gu, Chao; Hu, Shaojin; Zheng, Xusheng; Gao, Min‐Rui; Zheng, Ya‐Rong; Shi, Lei; Gao, Qiang; Zheng, Xiao; Chu, Wangsheng; Yao, Hong‐Bin; Zhu, Junfa; Yu, Shu‐Hong (Angewandte Chemie International Edition, 2018)
Ultrathin nanostructures are attractive for diverse applications owing to their unique properties compared to their bulk materials. Transition‐metal chalcogenides are promising electrocatalysts, yet it remains difficult to make ultrathin structures (sub‐2 nm), and the realization of their chemical doping is even more challenging. Herein we describe a soft‐template mediated colloidal synthesis of Fe‐doped NiSe2 ultrathin nanowires (UNWs) with diameter down to 1.7 nm. The synergistic interplay between oleylamine and 1‐dodecanethiol is crucial to yield these UNWs. The in situ formed amorphous hydroxide layers that is confined to the surface of the ultrathin scaffolds enable efficient oxygen evolution electrocatalysis. The UNWs exhibit a very low overpotential of 268 mV at 10 mA cm−2 in 0.1 m KOH, as well as remarkable long‐term stability, representing one of the most efficient noble‐metal‐free catalysts. Down to the wire: Colloidal Fe‐doped NiSe2 ultrathin nanowires (UNWs) down to 1.7 nm in diameter were synthesized by a binary soft‐template strategy. These UNWs yield surface‐confined electrochemical oxidation, enabling efficient and robust oxygen evolution catalysis owing to their favorable electronic structures and unsaturated local coordination environments.